Prevalence and Risk Factors of Hypertensive Retinopathy in Hypertensive Patients in a Tertiary Hospital of Gandaki Province of Nepal - Godar, Srijana Thapa; Kaini, Khem Raj (Journal of Lumbini Medical College, 2020)
Introduction: Hypertensive retinopathy is one of the major complications of hypertension. Presence of hypertensive retinopathy may be an indicator of presence of other complications too. This study aimed to determine the prevalence and risk factors of hypertensive retinopathy in hypertensive patients in a tertiary care hospital in Nepal. Methods: This was a hospital based cross-sectional study conducted among 95 hypertensive patients aged 30 years and above. Standard proforma was used to collect socio-demographic and clinical variables of the patients. Detailed eye examination including fundus evaluation under mydriasis was done on all patients and hypertensive retinopathy was graded according to Keith-Wagener-Barker classification. Statistical analysis was carried out using Epi-info 7. Results: The mean age of the study sample was 59.74±15.11 years. The prevalence of hypertensive retinopathy was 38.95%. Among the patients with hypertensive retinopathy, the prevalence of grade I, II, III and IV retinopathies were 7.36%, 17.89%, 10.52% and 3.15% respectively. There was statistically significant association between hypertensive retinopathy and controlled blood pressure and treatment of hypertension. However, there was no statistically significant association between hypertensive retinopathy and gender, duration of hypertension, residence, family history, history of smoking and diet. Conclusion: Uncontrolled blood pressure and untreated patients of hypertension were the significant risk factors for hypertensive retinopathy. Early diagnosis and treatment of hypertension is essential to prevent loss of vision.